Disparities exist between the dietary intake of Indigenous Australian women during pregnancy and the Australian dietary guidelines: the Gomeroi gaaynggal study. Issue 4 (26th March 2018) - Lee, Y. Q.; Collins, C. E.; Schumacher, T. L.; Weatherall, L. J.; Keogh, L.; Sutherland, K.; Gordon, A.; Rae, K. M.; Pringle, K. G.
Abstract: Background: Little is known about the adequacy of nutrient intakes and the overall diet quality of Indigenous Australian pregnant women. The aim of this cross‐sectional study was to assess nutrient sufficiency and diet quality, as measured using the Australian Recommended Food Score (ARFS), in pregnant women from the Gomeroi gaaynggal cohort ( n = 58). Methods: Maternal dietary intake during pregnancy was assessed using the Australian Eating Survey Food Frequency Questionnaire, which was self‐administered in the third trimester. Diet quality was determined using the ARFS. Food group servings and nutrient intakes were compared to the Australian Guide to Health Eating (AGHE) and Australian Nutrient Reference Values (NRVs). The current analysis examined the adequacy of usual intakes from food sources only, excluding supplements. Results: None of the women met all AGHE daily food group serving recommendations. The highest alignment rates were for dairy (33%), meat/alternatives (31%) and vegetables (29.3%). Almost 93% of participants exceeded the recommended intake of energy‐dense, nutrient‐poor foods and percentage energy from saturated fat was high (15%). Of the five key nutrients for optimal reproductive health (folate, iron, calcium, zinc and fibre), the nutrients with the highest percentage of pregnant women achieving the NRVs were zinc (77.6%) and folate (68.9%), whereas iron was the lowest. Only one person achieved all NRVs (folate, iron, calcium, zinc and fibre) important in pregnancy. The median ARFS was 28 points (maximum of 73). Conclusions: Although the small cohort limits the generalisability of the findings of the present study, the data obtained indicate that the diets of these Indigenous pregnant women are inadequate. Therefore, strategies aiming to optimise nutrient intakes of Indigenous pregnant women are needed urgently.